Pursuing an engineering major: social capital of women and underrepresented minorities. Issue 3 (3rd March 2020) - Skvoretz, John; Kersaint, Gladis; Campbell-Montalvo, Rebecca; Ware, Jonathan D.; Smith, Chrystal A. S.; Puccia, Ellen; Martin, Julie P.; Lee, Reginald; MacDonald, George; Wao, Hesborn
ABSTRACT: As part of a longitudinal research effort that examines the influence of social capital on differential persistence and retention among undergraduate engineering majors, this study examines how engineering degree-related social capital differs for first-year engineering students by gender and ethno-racial groups. Social capital is operationalized as a person's network of relationships with individuals who hold influential positions (e.g. parent, teacher, advisers) and access to resources that support persistence in engineering programs. Our data comprise survey responses from 2186 first-year engineering students, from eleven diverse colleges and universities, who provided information about their participation in engineering-related courses, activities, and programs while in high school as well as the individuals who influenced their decision to pursue an engineering major. We found few differences in social capital between men and women, but found many differences among ethno-racial groups, which suggests that different levels of social capital could influence students' persistence and retention.